2015
DOI: 10.2486/indhealth.2014-0073
|View full text |Cite
|
Sign up to set email alerts
|

Relationships (I) of International Classification of High-resolution Computed Tomography for Occupational and Environmental Respiratory Diseases with the ILO International Classification of Radiographs of Pneumoconioses for parenchymal abnormalities

Abstract: The International Classification of High-resolution Computed Tomography (HRCT) for Occupational and Environmental Respiratory Diseases (ICOERD) has been developed for the screening, diagnosis, and epidemiological reporting of respiratory diseases caused by occupational hazards. This study aimed to establish a correlation between readings of HRCT (according to the ICOERD) and those of chest radiography (CXR) pneumoconiotic parenchymal opacities (according to the International Labor Organization Classification/I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 19 publications
(19 reference statements)
0
27
0
1
Order By: Relevance
“…The radiologists utilized the International Classification of High-resolution Computed Tomography for Occupational and Environmental Respiratory Diseases (ICOERD) to classify and grade each study. The protocol and reliability of this classification have been documented 10, 11 . In brief, chest CT findings classified by this method include 8 main domains: well defined rounded opacities, irregular and/or linear opacities, ground glass opacities, honeycombing, emphysema, large opacities, inhomogeneous attenuation, and pleural abnormalities.…”
Section: Methodsmentioning
confidence: 99%
“…The radiologists utilized the International Classification of High-resolution Computed Tomography for Occupational and Environmental Respiratory Diseases (ICOERD) to classify and grade each study. The protocol and reliability of this classification have been documented 10, 11 . In brief, chest CT findings classified by this method include 8 main domains: well defined rounded opacities, irregular and/or linear opacities, ground glass opacities, honeycombing, emphysema, large opacities, inhomogeneous attenuation, and pleural abnormalities.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Suganuma et al it was shown that pulmonary specialists reported smaller opacities more often than radiologists18 ) . In another study, it was found that cases reported as mild emphysema using HRCT may have been reported as p opacity on chest x-ray results depending on the collecting effect19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Our study results suggest that the combination of lung function test, chest X-ray, and multiple biomarkers can improve the accuracy of screening for pneumoconiosis. The International Classification of High-resolution Computed Tomography for Occupational and Environmental Respiratory Diseases (ICORD) has been used for the screening and diagnosis of occupational disease [42]. We suggest that low-dose computed tomography can be used in high-risk workers who have been exposed to asbestos-contaminated minerals.…”
Section: Discussionmentioning
confidence: 99%